Psychology of Giftedness and the Theory of Positive Disintegration: A Conversation With Sal Mendaglio. Issue 4 (November 2019) - Mendaglio, Sal; Kettler, Todd; Rinn, Anne N.
Dąbrowski's theory of positive disintegration has been associated with the psychology of giftedness for four decades, and Sal Mendaglio has significantly contributed to the thoughtful understanding of the theory throughout those 40 years. In this interview, Mendaglio discusses the relationship between the theory of positive disintegration and the psychology of giftedness. Mendaglio addresses potential misunderstanding of the theory as well as the concept of overexcitabilities. He clarifies that Dąbrowski's theory is not a theory of giftedness; however, the theory as well as Dąbrowski's concept of intelligence contributed to Mendaglio's understanding of the psychology of giftedness. Mendaglio cautions against the oversimplification of overexcitabilities and the tools with which the construct has been measured.